DESIGN OF A WIRELESS SENSOR NETWORK FOR GREENHOUSES TEMPERATURE ANALYSIS - Barbosa, Rogério Zanarde; Perea Martins, João E. M. (IRRIGA, 2018)
DESIGN OF A Wireless Sensor Network FOR GreenhouseS Temperature Analysis Rogério Zanarde Barbosa1 and João EDUARDO MACHADO Perea Martins 2 1 Faculty of Higher Education and Integral Formation (FAEF), 17400-000, Garça-SP, Brazil. E-mail: rogeriozanarde@gmail.com. 2 Computer Science Department, School of Sciences (FC), São Paulo State University (UNESP), 17033-360, Bauru-SP, Brazil. E-mail: perea@fc.unesp.br. Orcid iD https://orcid.org/0000-0003-1056-497X 1 Abstract This work presents a wireless sensor network designed with fifteen temperature sensors to monitor this parameter variation inside a greenhouse, where all temperature values were transmitted by radio to a distant computer that records it into a database that allows a detailed temperature analysis. The results showed that the network operated efficiently in the greenhouse and allows more accurate definitions relative to the optimal sensor locations for extreme temperatures verification, and also allow a precise description of temperature variation over time. Keywords: WSN, climate, temperature, sensors Barbosa, R. G. and Perea Martins, J. E.M. PROJETO DE UMA rede de sensores sem fio PARA ANÁLISE DA TEMPERATURA EM CASAS DE vegetação 2 Resumo Este trabalho apresenta uma rede de sensores sem fio, projetada com quinze sensores de temperatura para monitorar a variação deste parâmetro dentro de uma estufa, onde todos os valores de temperaturas foram transmitidos por rádio para um computador remoto, no qual foi gravado um banco de dados para permitir uma análise detalhada deste parâmetro. Os resultados mostraram que a rede operou eficientemente na estufa e permite precisas definições relativas às localizações ótimas dos sensores para a verificação de temperaturas extremas e também permite uma descrição precisa da variação de temperatura ao longo do tempo. Palavras-chave: RSSF, clima, temperatura, sensores